2019
DOI: 10.1016/j.amepre.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Skin Tone Matters: Racial Microaggressions and Delayed Prenatal Care

Abstract: Introduction: Literature posits that discrimination can be a barrier to racial and ethnic minorities' healthcare use. This study examines the relationship between perceived discrimination in the form of racial microaggressions and delayed prenatal care in African American women. It also investigates whether this relationship is modified by women's shade of skin color owing to societal attitudes and beliefs tied to colorism (also known as skin-tone bias). Methods: Data were collected from a cohort of 1,410 blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…Experiences of discrimination in the health care system harm patients by negatively impacting trust, communication, and health-seeking behaviors. 13 , 16 , 32 , 33 Our findings underscore the importance of understanding aspects of patient identity, especially with regard to race/ethnicity, not as risk factors for discrimination or the downstream effects of those experiences; rather, exposure to discrimination and racism are the risks. 34 , 35 The prevalence of discrimination identified in this study points to a need to examine discrimination in the health care system as a risk factor for other negative effects.…”
Section: Discussionmentioning
confidence: 67%
“…Experiences of discrimination in the health care system harm patients by negatively impacting trust, communication, and health-seeking behaviors. 13 , 16 , 32 , 33 Our findings underscore the importance of understanding aspects of patient identity, especially with regard to race/ethnicity, not as risk factors for discrimination or the downstream effects of those experiences; rather, exposure to discrimination and racism are the risks. 34 , 35 The prevalence of discrimination identified in this study points to a need to examine discrimination in the health care system as a risk factor for other negative effects.…”
Section: Discussionmentioning
confidence: 67%
“…We also included season at blood draw, skin color and ethnicity, since these were hypothesized to be strongly related to vitamin D status and there is increasing evidence of an association with perinatal outcome. Seasonal variations in respiratory and viral infections, as well as in the temperature, impact on preterm birth [37][38][39][40], while skin color is related to ethnicity, which has an independent effect on preterm birth and SGA; recent research suggests that skin tone may also be directly relevant to the investigation of perinatal outcomes [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…These studies add to prior research, which has also identified significant direct associations between skin tone (machine or interviewer-rated), systolic blood pressure, hypertension, and cardio-metabolic health (Krieger, Sidney, and Coakley 1998; Wassink et al 2017). In fact, a recent study found links between skin tone and prenatal care (Slaughter-Acey et al 2019). Another recent study found significant associations between skin tone and hypertension between siblings using a family fixed-effects approach that even considered genetic pleiotropy—strong evidence of a robust relationship between being darker skinned and increased risk of hypertension among Blacks (Laidley et al 2019).…”
Section: Introductionmentioning
confidence: 99%